2015
DOI: 10.1111/bjd.13426
|View full text |Cite
|
Sign up to set email alerts
|

Stretch marks during pregnancy: a review of topical prevention

Abstract: Striae gravidarum (SG), or stretch marks developing during pregnancy, affect up to 90% of women. While not medically dangerous, SG can be disfiguring, causing emotional and psychological distress. However, studies specifically addressing the prevention of SG, especially during pregnancy, are sparse. Furthermore, the molecular pathogenesis of SG is unclear and may differ from that of striae from other causes. Considering these factors, we review topical modalities that have been used specifically for preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 41 publications
1
65
0
3
Order By: Relevance
“…Hyaluronic acid, the active ingredient in both creams, is thought to increase resistance to mechanical forces and oppose atrophy through stimulation of fibroblast activity and collagen production (Elsaie et al, 2009, Korgavkar and Wang, 2015). In both studies, the creams were applied through massage during the second trimester, which poses the question of whether the creams were truly beneficial or whether the results reflected the benefits of massage alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyaluronic acid, the active ingredient in both creams, is thought to increase resistance to mechanical forces and oppose atrophy through stimulation of fibroblast activity and collagen production (Elsaie et al, 2009, Korgavkar and Wang, 2015). In both studies, the creams were applied through massage during the second trimester, which poses the question of whether the creams were truly beneficial or whether the results reflected the benefits of massage alone.…”
Section: Resultsmentioning
confidence: 99%
“…SG presents as atrophic linear scars and can cause distress, often leading to a decrease in quality of life (Korgavkar and Wang, 2015, Park and Murase, 2013). SG are often overlooked as a cosmetic concern, which does not make the patient burden any less.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Topical tretinoin improve the appearance of striae rubra significantly [19][20][21][22] ; however, it is contraindicated in breastfeeding or pregnant women due to its probable teratogenic side effects. 23,24 Several studies have reported the improvement of the clinical appearance of striae with 585-nm pulsed dye laser (PDL) via enhancement of the extracellular matrix collagen. [25][26][27][28] In addition, it has a modest efficacy in decreasing the erythema of striae rubra; however, it has [29][30][31][32] More recently, there has been evidence that indicates the benefits of both fractionated non-ablative and ablative lasers in increasing collagen fibers, and improving the appearance of striae alba.…”
Section: Introductionmentioning
confidence: 99%
“…), dėl kurių oda ruožais pakeičia natūralų atspalvį. Rašoma, kad pagal genetinius veiksnius galima prognozuoti ne tik strijų atsiradimą, bet jų išvaizdą [1][2][3] Nustatyta, kad moterims, kurių didesnis kūno masės indeksas, ir moterims, nešiojančioms didesnius kūdikius, strijos atsiranda dažniau [4 -6]. Buvo nustatytas reikšmingas ryšys tarp strijų atsiradimo ir nėščiųjų amžiaus bei svorio, įgyto nėštumo metu, pilvo ir šlaunų perimetro padidėjimo ar rūkymo [7], bet buvo gauta prieštaringų duomenų, nepatvirtinančių nei šeimos genetikos, nei kūno masės indekso prieš nėštumą, nei svorio priaugimo nėštumo metu reikšmės strijoms atsirasti [8].…”
Section: įVadasunclassified